Functional relationship of Phomopsis leaf blight of eggplant with environmental factors and a linear model for predicting the disease - SITANSU PAN, S. J. ISLAM and (Indian Phytopathology, 2012)
Effect of environmental factors (x, i = 1-6) on Phomop sis leaf blight severity (Y) in eggplant under natural epiphytotics were analysed for predictive purposes. Correlation analysis of the variables showed that maximum temperature (Xl)' minimum temperature (X z )' minimum relative humidity (X 4), total rainfall (X s)'and number of rainy days (X 6) had a significant (P :s 0.01) positive correlation (r = 0.6890-0.8416) with disease severity. There was non-significant negative correlation between disease severity and maximum relative humidity (X3). The Xi'S also showed multicolinearity among themselves. Regression of Y on each of the individual x.'s revealed that the best fit relations between the former and the latter could be expressed in the form of cub'ic for XI.(RZ = 0.6946), Xz (RZ = 0.7475), and X 4 (R2' = 0.6895); second degree polynomial for X, (R Z = 0.5906); and linear for X6 (RZ = 0.6894). In multiple regression analysis, the linear prediction equation Y = 11.6531-1.0096 Xl + 1.4490 X, + 2.9738 X6 gave maximum fitness for fair degree of predictability of Phomopsis leaf blight severity where, Xl = fortnightly mean of maximum temperature, X, = fortnightly mean minimum temperature, and X6 = number of rainy days in a fortnight. This prototype model requires multilocational test for its validity.